Peran Pengendalian Internal dalam Mewujudkan Keberlanjutan Keuangan Pemerintah Daerah di Indonesia - Paundanan, Grayesta; Tenripada, Tenripada; Yunia, Latifah Sukmawati; Furqan, Andi Chairil; Yudistira, Fajar Gilang (CURRENT: Jurnal Kajian Akuntansi dan Bisnis Terkini, 2026)
This study examines the differentiated impacts of the Government Internal Control System (SPIP) and the Regional Government Internal Supervisory Apparatus (APIP) on local government financial sustainability in Indonesia. Using secondary data from 2,690 observations of provincial, city, and regency governments during 2018–2022, this study employs multiple regression analysis. The findings show that APIP has a significant positive effect on efficiency and effectiveness, but a significant negative effect on equity in financial management. In contrast, SPIP is found to significantly influence only the efficiency dimension. This study contributes novel empirical evidence that internal control mechanisms do not affect financial sustainability uniformly, but instead play differentiated roles across efficiency, effectiveness, and equity dimensions. By integrating Agency Theory and Legitimacy Theory, this study provides a clearer theoretical explanation of how APIP and SPIP address agency problems and legitimacy pressures in local government financial management. The results suggest that while APIP enhances resource optimization, it faces challenges in ensuring equitable fund distribution. Therefore, local government financial sustainability can be strengthened through targeted optimization of SPIP and reinforcement of APIP’s supervisory role, particularly in promoting distributive justice.